Electronic practicum assessment system based on android at politeknik ATI makassar. Issue 1 (July 2020) - Habibuddin, J; Suhaebri, T; Ainuddin, A; Azis, M F; Mutmainnah,
Abstract: The Practicum assessment conducted conventionally is gradually replaced with an Android-based system. It aims to support the government program of Making Indonesia 4.0. In this research, the electronics practicum assessment is designed using the App Inventor application. The attendance assessment and initial assignment are designed to obtain an objective grade. Attendance assessment is conducted by making a standard assessment form, determining points obtained by looking at the time of arrival. Assessing the initial task was done by making ten multiple-choice questions for each experiment. The initial assignment assessment form was created in Microsoft Excel to make it easier to import, export data to .csv (comma separated values) to enter the database system. The results obtained from 6 types of initial assignment assessment experiments conducted using the application. There were 5 trials that were successfully run, and there was still one error trial.